Participation in public programmes for innovation support in manufacturing industry in Peru - Afcha, S.M.; Chu, M. (Taylor and Francis Ltd., 2024)
This paper analyses the participation of Peruvian companies in public programmes for innovation support promoted by the Peruvian government from 2012 to 2014. Specifically, it examines the characteristics of firms that are informed about these programmes and, more importantly, the motives leading them to apply for this support. Using data from the 2015 National Survey of Peruvian Innovation in manufacturing firms, we find that knowledge about programmes is positively influenced by variables related to the percentage of qualified employees, R&D intensity, and their links with other agents. Firms with higher R&D intensity, are also more likely to apply for public support, together with firms perceiving the lack of external funds as an important innovation obstacle, while variables such as the perception of high cost of innovation and the utilized installed capacity, reduce the likelihood of application. These findings partially coincide with the previous empirical literature. Finally, the association between R&D intensity and public support is examined. Results show that total public support is associated with higher R&D intensity of supported firms, while in the case of only-funded programmes, non significant effects were found.
Keywords: Obstacle; Public support; Government (linguistics); Business; Perception; R&D intensity; Marketing; Survey data collection; Industrial organization; Public economics; Economics; Political science; Management; Psychology; https://purl.org/pe-repo/ocde/ford#5.02.02